2014
DOI: 10.1038/ncomms6409
|View full text |Cite
|
Sign up to set email alerts
|

Large-scale analysis of lysine SUMOylation by SUMO remnant immunoaffinity profiling

Abstract: Small ubiquitin-related modifiers (SUMO) are evolutionarily conserved ubiquitin-like proteins that regulate several cellular processes including cell cycle progression, intracellular trafficking, protein degradation and apoptosis. Despite the importance of protein SUMOylation in different biological pathways, the global identification of acceptor sites in complex cell extracts remains a challenge. Here we generate a monoclonal antibody that enriches for peptides containing SUMO remnant chains following tryptic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
119
0
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 119 publications
(126 citation statements)
references
References 43 publications
(58 reference statements)
6
119
0
1
Order By: Relevance
“…In accordance with the His 6 precipitation data presented here, previous reports suggest that only SUMO1 is conjugated to EXOSC10; multiple mass spectrometry analyzes of affinity tagged SUMO1 conjugates, but not SUMO2 or SUMO3, identified EXOSC10 as a SUMO target (Zhao et al 2004;Matic et al 2010;Westman et al 2010;Impens et al 2014;Lamoliatte et al 2014). In accordance with this, a screen of the endogenous SUMOylated proteome identified EXOSC10 conjugation to SUMO1 but not SUMO2 (Becker et al 2013).…”
Section: Implications Of Exosc10 Sumoylationsupporting
confidence: 92%
See 1 more Smart Citation
“…In accordance with the His 6 precipitation data presented here, previous reports suggest that only SUMO1 is conjugated to EXOSC10; multiple mass spectrometry analyzes of affinity tagged SUMO1 conjugates, but not SUMO2 or SUMO3, identified EXOSC10 as a SUMO target (Zhao et al 2004;Matic et al 2010;Westman et al 2010;Impens et al 2014;Lamoliatte et al 2014). In accordance with this, a screen of the endogenous SUMOylated proteome identified EXOSC10 conjugation to SUMO1 but not SUMO2 (Becker et al 2013).…”
Section: Implications Of Exosc10 Sumoylationsupporting
confidence: 92%
“…Indeed, other exosome subunits appear in screens for SUMOylated proteins, such as EXOSC5 (Becker et al 2013;Hendriks et al 2015) and EXOSC9 (Golebiowski et al 2009;Impens et al 2014;Lamoliatte et al 2014;Hendriks et al 2015). Furthermore, SUMO site prediction tools identify putative sites in EXOSC2, EXOSC3, EXOSC7, EXOSC8, and EXOSC9 (Zhao et al 2014) and SUMOplot.…”
Section: Implications Of Exosc10 Sumoylationmentioning
confidence: 99%
“…The covalent attachment of the small SUMO moiety to substrate proteins has recently emerged as a main regulatory system, leading to dramatic changes in the SUMO proteome (31)(32)(33)(34) with consequences on IFN responses and antiviral defense mechanisms (9,10,27).…”
Section: Discussionmentioning
confidence: 99%
“…In recent years, several efforts have been made to study sumoylation on a global and site-specific manner by high resolution mass spectrometry (14,15,(51)(52)(53)(54). Reanalyzing all these available data sets (13) revealed that at physiological conditions, at least half of the SUMO substrates are modified at the minimal KxE motif, although upon stress, more lysines at non-SCM sites are modified.…”
Section: The Sumo Consensus Motifmentioning
confidence: 99%